Structural evolution analytics of public rest APIS (2022)
The use of technology has had an exponential growth curve that has driven different services to be offered through the Internet to solve the needs of multiple customers. Among the different existing services offered through the World Wide Web, there are APIs (Application Programming Interfaces) that allow consumers to access information of a certain nature, functions predefined by providers that are useful for a certain audience, among other functionalities that are consumed by a client¿s software. APIs can be classified as libraries or as remote APIs considering the place where they are hosted. Library APIs run in the same environment as the client software, while remote APIs are hosted in a different environment and are accessed by the client application through remote access protocols. This paper focuses on REST Web APIs (remote APIs) which are the most common type of Web APIs. This is because they are very easy to understand and integrate with client code. It is worth mentioning that REST is a software architectural style that guides the design and development of the architecture of a software or related for the Internet. Therefore, a REST API is an architecture for an API that uses HTTP-like requests to access data and perform interactions.